Profanity in Suicide Squad and Deadpool 2: A Study of Translation Techniques - Annisa Fadilla Hanan (Universitas Pendidikan Indonesia (UPI), 2019)
This study aims to find out the translation techniques used by the translator to do the act of censorship in translating the subtitle in Suicide Squad and Deadpool 2 movies. This study also analyzes the translation shift in the subtitle and acceptability of the translation. This study employs a qualitative method of data collection and analysis informed by Pinker’s (2007) profanity classification according to its purpose, Molina and Albir’s (2002) concept of translation and Newmark’s (1988; 1981) concept of transposition and translation acceptability. The study found five types of profanity based on its purpose in 213 utterances spoken by the movie characters and 11 translation techniques applied to those utterances. Those five types of profanity include idiomatically, abusively, cathartically, descriptively, and emphatically in the two movies. The study also found four types of translation shifts (automatic, grammatical structure, natural grammatical, lexical gap) as a means of maintaining the meanings of the source language (SL). The meanings shift as a result of an act of translation censorship strategies. The study shows that transferring meaning into other languages such as in the process of subtitling translation could incur potential changes in meaning. Keywords: censorship, profanity, translation techniques, translation shift, translation acceptability.